Infantile Neuroaxonal Dystrophy in Two Cases: Siblings with Different Presentations - Ansari, Behnaz; Nasiri, Jafar; Namazi, Hamide; Sedghi, Maryam; Afzali, Mahdieh (Iranian Journal of Child Neurology, 2022)
Infantile neuroaxonal dystrophy (INAD) is a rare recessive neurodegenerative disorder manifested by symptoms, including hypotonia, extrapyramidal signs, spastic tetraplegia, vision problems, cerebellar ataxia, cognitive complications, and dementia, before the age of three. Various reports evaluated the relationship with the incidence of INAD and different mutations in the PLA2G6 gene. We describe cases of two children with INAD whose diagnoses were challenging due to misleading findings and had a mutation in the position C.2370 T>G (p. Y790X) in the PLA2G6 gene based on NM_001349864 which has been reported previously.